Bioprotective properties of Dragon's blood resin: In vitro evaluation of antioxidant activity and antimicrobial activity - Gupta, Deepika (BioMed Central, 2011)
BACKGROUND: Food preservation is basically done to preserve the natural characteristics and appearance of the food and to increase the shelf life of food. Food preservatives in use are natural, chemical and artificial. Keeping in mind the adverse effects of synthetic food preservatives, there is a need to identify natural food preservatives. The aims of this study were to evaluate in vitro antioxidant and antimicrobial activities of Dragon's blood resin obtained from Dracaena cinnabari Balf f., with a view to develop safer food preservatives. METHODS: In this study, three solvents of varying polarity were used to extract and separate the medium and high polarity compounds from the non-polar compounds of the Dragon's blood resin. The extracts were evaluated for their antimicrobial activity against the food borne pathogens. The antioxidant activities of the extracts were assessed using DPPH and ABTS radical scavenging, FRAP, metal chelating and reducing power assays. Total phenolics, flavonoids and flavonols of extracts were also estimated using the standard methods. RESULTS: Phytochemical analysis of extracts revealed high phenolic content in CH(2)Cl(2 )extract of resin. Free radical scavenging of CH(2)Cl(2 )extract was found to be highest which is in good correlation with its total phenolic content. All test microorganisms were also inhibited by CH(2)Cl(2 )extract. CONCLUSIONS: Our result provide evidence that CH(2)Cl(2 )extract is a potential source of natural antioxidant compounds and exhibited good inhibitory activity against various food borne pathogens. Thus, CH(2)Cl(2 )extract of Dragon's blood resin could be considered as possible source of food preservative.